2019
DOI: 10.1111/all.13848
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of de‐labeling penicillin allergy

Abstract: Background Even though 8%‐25% of most populations studied globally are labeled as penicillin allergic, most diagnoses of penicillin allergy are made in childhood and relate to events that are either not allergic in nature, are low risk for immediate hypersensitivity, or are a potential true allergy that has waned over time. Penicillin allergy labels directly impact antimicrobial stewardship by leading to use of less effective and broader spectrum antimicrobials and are associated with antimicrobial resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
160
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(186 citation statements)
references
References 151 publications
(441 reference statements)
2
160
0
8
Order By: Relevance
“…Such re-evaluation is crucial considering the large number of patients who could be avoiding NSAIDs despite being no longer hypersensitive 119,120 as occurs with other drugs. 121,122 Whether tolerance persists or whether repetitive NSAIDs contacts could re-induce hypersensitivity is unknown. In addition, it is unclear whether patients maintaining NSAIDs hypersensitivity represent a different NIUA subphenotype and whether they would also lose hypersensitivity.…”
Section: Niuamentioning
confidence: 99%
“…Such re-evaluation is crucial considering the large number of patients who could be avoiding NSAIDs despite being no longer hypersensitive 119,120 as occurs with other drugs. 121,122 Whether tolerance persists or whether repetitive NSAIDs contacts could re-induce hypersensitivity is unknown. In addition, it is unclear whether patients maintaining NSAIDs hypersensitivity represent a different NIUA subphenotype and whether they would also lose hypersensitivity.…”
Section: Niuamentioning
confidence: 99%
“…Previous work has clearly demonstrated that beta-lactam allergy labels directly impact antimicrobial stewardship by leading to use of broader spectrum, less effective antimicrobials and are associated with antimicrobial resistance, higher costs, and delays in care. 37 Our findings suggest that for patients with chronic back pain, having a reported NSAID allergy is associated with a higher risk of receiving other analgesic medications, including opioids. Many NSAIDs are available over-the-counter and less costly than alternative drugs such as opioids or tricyclic antidepressants.…”
Section: Discussionmentioning
confidence: 64%
“…Firstly, there were marginally more respondents who answered to do skin testing for cephalosporins than penicillins. This may be a reflection of the increasing use of cephalosporins in Asia and hence increase in DHR [59]; intermittent difficulties in accessing commercial PPL and minor determinants, and emerging safety data of direct amoxicillin oral provocation tests in low-risk patients without the need for prior skin testing [60]. Secondly, iodinated contrast media (ICM) has now emerged as one of the "new" drugs for which skin testing has become increasingly used, likely for several reasons.…”
Section: Discussionmentioning
confidence: 99%